2014
DOI: 10.1017/s1755691014000218
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of the Silurian osteostracans of the East Baltic

Abstract: The sculpture and histology of osteostracan head shields and trunk squamations from the Silurian of Estonia are described, illustrated and used for the identification of disarticulated microremains collected from outcrop sections and numerous drill cores in Estonia and Latvia over the last 40 years. The scattered osteostracan material contains thousands of specimens of scales and shield fragments. The sculpture and histology of species of the previously identified eight genera in the region (Tremataspis, Dartm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(106 citation statements)
references
References 56 publications
8
93
1
4
Order By: Relevance
“…This diversity peak is more or less contemporaneous in both the Eastern Baltic region and Gotland (Sweden), but equally diverse faunas have been reported from younger sediments of the East Baltic (Blom et al, 2002;Märss et al, 2007Märss et al, , 2014. Thelodonts seem to have spread across a wide range of environments (Märss et al, 2007), but facies associations of anaspids and osteostracans indicate that these groups preferred lagoon and shoal areas (Märss and Einasto, 1978;Sansom, 2008;Märss et al, 2014). Sansom (2008) suggested that our understanding of early osteostracan evolution is largely obscured by the taphonomic bias resulting from their seemingly specific environmental preferences during the Silurian.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…This diversity peak is more or less contemporaneous in both the Eastern Baltic region and Gotland (Sweden), but equally diverse faunas have been reported from younger sediments of the East Baltic (Blom et al, 2002;Märss et al, 2007Märss et al, , 2014. Thelodonts seem to have spread across a wide range of environments (Märss et al, 2007), but facies associations of anaspids and osteostracans indicate that these groups preferred lagoon and shoal areas (Märss and Einasto, 1978;Sansom, 2008;Märss et al, 2014). Sansom (2008) suggested that our understanding of early osteostracan evolution is largely obscured by the taphonomic bias resulting from their seemingly specific environmental preferences during the Silurian.…”
Section: Introductionmentioning
confidence: 84%
“…Furthermore, there are a number of remains with osteostracan and anaspid affinities that are too worn or too fragmentary to be identified. The majority of the vertebrates found in this study have already been described from Gothemshammar or figured in open nomenclature (Martinsson, 1966;Gross, 1968;Fredholm, 1990;Blom et al, 2002;Märss et al, 2014), and our descriptions focus on the new scale types and sculpture patterns belonging to taxa not reported from Gothemshammar before.…”
Section: Vertebratesmentioning
confidence: 92%
See 3 more Smart Citations